Implications of Processed Wood Export Performance for Regional Tax Income and Supporting Wood Industry MSMe Development in Indonesia - Feridah Feridah; Darwati Susilastuti; Pudji Astuty (PT. Publikasiku Academic Solution, 2026)
The processed wood export sector plays a strategic role in Indonesia's regional economies, yet its broader developmental impacts beyond direct foreign exchange earnings remain underexplored. As forestry sector performance fluctuates across provinces between 2016 and 2024, understanding how export activities stimulate local revenue generation and support the growth of wood industry MSMEs has become increasingly important for sustainable regional development planning. This study aims to analyze the implications of Indonesian processed wood export performance on regional tax revenue and the development of supporting wood industry MSMEs. The research employs a quantitative approach using panel data regression analysis. The sample comprises 10 provinces in Indonesia observed annually from 2016 to 2024, with data sourced from Statistics Indonesia (BPS), the Ministry of Finance, and relevant regional government agencies. The results of the panel data regression indicate that Indonesian processed wood export performance has a significant and positive impact on both regional tax revenue and the development of supporting wood industry MSMEs. These findings suggest that increased export activity generates substantial spillover effects that benefit local economies through enhanced tax contributions from the forestry value chain, while simultaneously creating opportunities for MSME growth in upstream and downstream activities such as raw material supply, transportation, processing services, and marketing.